Pemilihan Abang Kakak Tebing Tinggi dengan Metode Profile Matching Berbasis Website - Harahap, Frans Adetya; Ali Ikhwan; Dedi Irawan, Muhammad (METIK JURNAL (AKREDITASI SINTA 3), 2025)
In today's digital era, advances in information technology have brought about major transformations in various aspects of life, including in the decision-making process in the social field. One of the important activities for the young generation in Tebing Tinggi City is the selection of Abang Kakak Tebing Tinggi as a representation of regional culture and potential. The conventional selection process that has been used so far often takes a long time and is not entirely objective. Therefore, this study designs a web-based decision support system using the Profile matching method. This system facilitates participant assessment based on the level of conformity between ideal criteria and actual profiles. The implementation results show that the system provides transparent and fair recommendations. System testing shows a good level of calculation accuracy, with the highest score for male participants being 4.58 and female participants being 4.42. With the blackbox testing method, all system features are also proven to run as they should.